2023
DOI: 10.3389/fpls.2023.1140727
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide survey and expression analysis of Dof transcription factor family in sweetpotato shed light on their promising functions in stress tolerance

Abstract: DNA-binding with one finger (Dof) transcription factors play a crucial role in plant abiotic stress regulatory networks, although massive Dofs have been systematically characterized in plants, they have not been identified in the hexaploid crop sweetpotato. Herein, 43 IbDof genes were detected to be disproportionally dispersed across 14 of the 15 chromosomes of sweetpotato, and segmental duplications were discovered to be the major driving force for the expansion of IbDofs. The collinearity analysis of IbDofs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 57 publications
3
10
0
Order By: Relevance
“…Similar situations were also reported in the PYLs from apple, cucumber, Medicago sativa, and Prunus avium [14,36,39,41]. Moreover, there is the largest number of collinear gene pairs between I. batatas and I. trifida, I. triloba, indicating that their two diploid wild relatives play key roles in the evolution of sweetpotato PYL genes, which is consistent with that of our previous reports of multiple transcription factor families [28,38,42].…”
Section: Discussionsupporting
confidence: 91%
“…Similar situations were also reported in the PYLs from apple, cucumber, Medicago sativa, and Prunus avium [14,36,39,41]. Moreover, there is the largest number of collinear gene pairs between I. batatas and I. trifida, I. triloba, indicating that their two diploid wild relatives play key roles in the evolution of sweetpotato PYL genes, which is consistent with that of our previous reports of multiple transcription factor families [28,38,42].…”
Section: Discussionsupporting
confidence: 91%
“…In addition to the E group, the D1 subgroup, also known as the CDF subfamily, contains the most Dof genes, including DhDof2 , DhDof20 , DhDof12 , and DhDof16 . AtDof1.4 was classified into Group IV or B2 subgroups in previous studies ( Yanagisawa, 2002 ; Lijavetzky et al, 2003 ; Zhang et al, 2023 ). However, the phylogenetic trees in our study indicated that AtDof1.4 did not group with AtDof1.7, AtDof3.1, AtDof3.4, and AtDof5.8 in the D2 subgroup but as an independent subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…D. Huoshanense materials were collected at the Plant Cell Engineering Center of West Anhui University (Luan, China). The culture conditions were 25°C ± 2°C, with a 12 h day and 12 h dark cycle ( Zhang et al, 2023 ). MS medium (without hormone addition) was used for the tissue culture of seedlings.…”
Section: Methodsmentioning
confidence: 99%
“…The comparative genome-wide study was performed between four Ipomoea species to evaluate valine glutamine motif-containing genes and found 40 differentially expressed genes (DEGs) referring to various abiotic stresses [ 26 ]. The other genome-wide studies in different Ipomoea species were conducted for important TF families such as NAC ( NAM , ATAF , and CUC ) TFs family [ 27 ], hydroxycinnamate-CoA quinate hydroxycinnamoyl transferase gene family [ 28 ], DNA-binding with one finger (Dof) TF family [ 29 ], myeloblastosis (MYB) gene family [ 30 ], phytochrome-interacting factors [ 25 ], domain of unknown function gene family [ 31 ], two-component system genes [ 32 ], xyloglucan endotransglucosylase/hydrolase gene family [ 33 ], expansin gene family [ 34 ], glycine-rich RNA-binding proteins [ 35 ], WRKY TFs family [ 36 ], zinc-finger domain-containing stress-associated proteins [ 37 ], plant-specific GRAS TFs [ 38 ], APETALA2/ethylene responsive factor (AP2/ERF) TFs family [ 38 ], jasmonate-ZIM (JAZ) TF family [ 39 ], and bZIP TF family [ 10 ]. These studies provide new insights for understanding the different TFs families-mediated stress responses and lays the foundation for future functional investigation of sweet potato TFs families.…”
Section: Genome-wide Survey Of Tf Families and Their Response To Vari...mentioning
confidence: 99%